The inspirational and aspirational desires of Ridzuan / Sharifah Zannierah Syed Marzuki ... [et al.] - Syed Marzuki, Sharifah Zannierah; Yahya, Wan Kalthom; Buyong, Siti Zahrah; Ahmad Zaini, Azniza; Ali, Roslina (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
The inspiration to grow big in business has initiated Ridzuan Yahya, the founding entrepreneur of RVCOMS Sdn. Bhd. to register his business in 2019. RVCOMS is a trading company that obtains its Virgin Coconut Oil (VCO) from Indonesia and sells to various international clients that include the United States and United Kingdom. As a trader in Business to Business (B2B), Ridzuan deals with neighbouring suppliers that hold the price of the resources and buyers of different business natures at international levels. Price wars between competitors and RVCOMS is something to worry about as well as maintaining the quality supplies of the resources but Ridzuan has his own strategies to overcome the challenges. As a newcomer in VCO trading business, Ridzuan is optimistic that RVCOMS has the potential to move forward with or without his presence in the future. His intention to register his business for Initial Public Offering (IPO) is one of the ways to maintain the sustainability of his business.